Legal rights and moral rights / Matthew H. Kramer. - Kramer, Matthew H., 1959- (Cambridge elements. Elements in the philosophy of law, 2025)
In a short span, this Element will delineate the general nature of legal and moral rights and the general nature of the holding of rights, and it will also sketch the justificatory foundations of rights. Hence, the Element will treat of some major topics within legal, political, and moral philosophy as it combines analytical theses and ethical theses in a complex pattern.